2015
DOI: 10.1515/text-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Thematic choice and progression in English and Chinese radio news texts: a systemic functional analysis

Abstract: This paper reports on a comparative study of thematic choice and progression in English and Chinese radio news texts, conducted within the systemic functional theory of Theme-Rheme (Halliday and Matthiessen 2004) and the thematic progression model evolving from Daneš's work in the 1970s. It is suggested, following a detailed analysis of a corpus of sixty English and Chinese texts, that there are some similarities and disparities in structuring thematic information between the two languages. Overall, the key di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Based on its type, the Unmarked Topical Theme, constituted by subjects dominated by a noun phrase and pronoun, is mostly applied by the students. It is comparable to studies conducted by Bangga (2013), Februana (2014), Jalilifar (20092010), Safitra (2013), Ping (2007), Thalib (2014), Liu & Tucker (2015), Marfuaty andWahyudi (2015), Sianipar (2015), Narita (2016), andJing (2015) which found that subject is typical unmarked Topical Theme in students' writings. Meanwhile, only very limited numbers of marked Topical Themes constituted by dependent clauses, prepositional phrases, and adverbial groups existed as thematic heads observed the essays.…”
Section: Thematic Choicesupporting
confidence: 85%
See 2 more Smart Citations
“…Based on its type, the Unmarked Topical Theme, constituted by subjects dominated by a noun phrase and pronoun, is mostly applied by the students. It is comparable to studies conducted by Bangga (2013), Februana (2014), Jalilifar (20092010), Safitra (2013), Ping (2007), Thalib (2014), Liu & Tucker (2015), Marfuaty andWahyudi (2015), Sianipar (2015), Narita (2016), andJing (2015) which found that subject is typical unmarked Topical Theme in students' writings. Meanwhile, only very limited numbers of marked Topical Themes constituted by dependent clauses, prepositional phrases, and adverbial groups existed as thematic heads observed the essays.…”
Section: Thematic Choicesupporting
confidence: 85%
“…The limited use of the Interpersonal Theme is related to the nature of the text. Ping (2007), Sianipar (2015), and Undayasari & Saleh's (2015) found that this Theme occurred in exposition texts, while its occurrence is rarely observed in scientific books (Jalilifar, 2009) and English news texts (Liu & Tucker, 2015) and advertorials (Thalib, 2014). In other words, the occurrence of interpersonal Theme is determined by the nature of the texts.…”
Section: Thematic Choicementioning
confidence: 99%
See 1 more Smart Citation
“…A number of scholars have explored the relationship between TP patterns and different text types [10][11][12][13]. Meanwhile, some scholars focus on narrations and argumentations.…”
Section: Literature Reviewmentioning
confidence: 99%